Parametric calibration of the Hargreaves–Samani equation for use at new locations - Shahidian, Shakib (2014)
The Hargreaves–Samani (HS) evapotranspiration equation is very useful for the on-site irrigation management in data-short situations such as small and midsize farms and landscaped areas. Although much work has been performed to improve the precision of the evapotranspiration (ETo) estimates for use at new locations, the results have not been consistent and many have not been confirmed by other works. The purpose of this study was to review and to evaluate the seven most promising parameters used for the calibration of the HS evapotranspiration equation, using two different regions: California and Bolivia. The results of this study show that annual correlations between HS and Penman–Monteith can be misleading because the correlation is poor in the humid months and improves progressively along the dry season until the first rains. The average monthly wind speed can be used for both spatial and seasonal calibration of the HS equation, especially during the irrigation season. Elevation and precipitation can be used to calibrate the HS equation when no reference ETo values are available at nearby stations. The monthly value of KT calculated from solar radiation follows a parabolic function along the year and should not be used for improving the estimates of the HS equation because the clearness index produces better results than actual solar radiation measurements. The results also indicate that the use of distance to coast, temperature range and temperature parameter does not improve the precision of the HS equation